A case study of healthcare providers' goals during interprofessional rounds. Issue 4 (4th July 2017) - Prystajecky, Michael; Lee, Tiffany; Abonyi, Sylvia; Perry, Robert; Ward, Heather
ABSTRACT: Daily interprofessional rounds enhance collaboration among healthcare providers and improve hospital performance measures. However, it is unclear how healthcare providers' goals influence the processes and outcomes of interprofessional rounds. The purpose of this case study was to explore the goals of healthcare providers attending interprofessional rounds in an internal medicine ward. The second purpose was to explore the challenges encountered by healthcare providers while pursuing these goals. Three focus groups were held with healthcare providers of diverse professional backgrounds. Focus group field notes and transcripts were analysed using thematic analysis. The data indicated that there was no consensus among healthcare providers regarding the goals of interprofessional rounds. Discharge planning and patient care delivery were perceived as competing priorities during rounds, which limited the participation of healthcare providers. Nevertheless, study participants identified goals of rounds that were relevant to most care providers: developing shared perspectives of patients through direct communication, promoting collaborative decision making, coordinating care, and strengthening interprofessional relationships. Challenges in achieving the goals of interprofessional rounds included inconsistent attendance, exchange of irrelevant information, variable participation by healthcare providers, and inconsistent leadership. The findings of this study underscore the importance of shared goals in the context of interprofessional rounding.